Socio demography of mental retardation: A community-based study from a goitre zone in rural sub-Himalayan India - Sharma, Shailja (J Neurosci Rural Pract, 2015)
INTRODUCTION: Mental retardation is one of the most common disabilities of childhood which can be prevented by timely identification of the causative agent and an adequate management accordingly. District Kangra lies in the sub-Himalayan belt and forms a part of the 2400 km long goitre belt along the southern slopes of the Himalayas. OBJECTIVE: To study the prevalence of mental retardation among children (1–10) years of age. MATERIALS AND METHODS: A two-phase cross-sectional study was conducted in the rural area of district Kangra. A 30-cluster sampling technique was used to screen a population of children 1–10 years of age from five randomly selected panchayats (village government units) of district Kangra. The screening was based on a modified version of the ten questions screen, adapted to the local population. In the first phase a door to door survey was done to identify suspects of mental retardation. In the second phase, the children found positive in the first phase were called for examination by the pediatrician to confirm mental retardation. RESULTS: A total of 2420 children were screened in the first phase of which 95 tested positive. About 52 of these children were found to be mentally retarded in the second phase giving a prevalence of 2.15%. The 69% of these children belonged to the lower middle class and 28.3% belonged to middle class families using the Uday Parekh scale for assessment of the socio-economic status. CONCLUSION: Prevalence of mental retardation is high in district Kangra of Himachal Pradesh in comparison to other states of India. This could be attributed to the good primary health care in Himachal Pradesh where institutional deliveries are about 70%. This may have led to better survival of children with congenital disorders and those that suffer perinatal trauma.